Innovation is the focus in UMP’s business engineering course - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) was one of the project partners involved in organising the International Business Engineering Conference (IBEC 2016) on September 26, 2016 recently.